2016
DOI: 10.1016/j.foodchem.2016.05.097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing moisture on the physical properties and in vitro digestibility of starch and protein in extruded brown rice and pinto bean composite flours

Abstract: The influence of pinto bean flour and processing moisture on the physical properties and in vitro digestibility of rice-bean extrudates has been investigated. Brown rice: pinto bean flour (0%, 15%, 30%, and 45% bean flour) were extruded under 5 moisture conditions (17.2%, 18.1%, 18.3%, 19.5%, and 20.1%). Physical properties [bulk density, unit density, radial expansion, axial expansion, overall expansion, specific volume, hardness, color, water solubility index, and water absorption index] and in vitro starch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 33 publications
7
36
0
3
Order By: Relevance
“…This effect is due to the fact that higher moisture content decreases the shear of the plasticized mass inside the extruder, reducing the gelatinized starch and prevent the growth of air bubbles of the snacks (Stojceska et al, 2009;Sumargo et al, 2016). The hardness of the snacks ranged from 14.1 to 32.8 N. Similar results (16.2 to 43.4 N) were reported by Joshi et al (2014) on corn extrudates added with microalga.…”
Section: Hardnesssupporting
confidence: 63%
See 4 more Smart Citations
“…This effect is due to the fact that higher moisture content decreases the shear of the plasticized mass inside the extruder, reducing the gelatinized starch and prevent the growth of air bubbles of the snacks (Stojceska et al, 2009;Sumargo et al, 2016). The hardness of the snacks ranged from 14.1 to 32.8 N. Similar results (16.2 to 43.4 N) were reported by Joshi et al (2014) on corn extrudates added with microalga.…”
Section: Hardnesssupporting
confidence: 63%
“…LEB 18. Previous studies also used rice as raw material and observed similar behavior of moisture on the expansion of extrudates (Borah et al, 2016;Sumargo et al, 2016). According to Ding et al (2005) increasing feed moisture content during extrusion reduces the mechanical energy dissipation, resulting in the mass less viscous, reducing the degree of gelatinization of the starch and resulting in less expansion.…”
Section: Expansion Indexmentioning
confidence: 80%
See 3 more Smart Citations